Studies on the grinding force, size effect, surface texture, and mechanism of material removal in the grinding of AA6061-TiB2/ZrB2 in situ composite. Issue 2 (November 2019) - Mahamani, A.
Abstract: Machining and conversion of aluminum matrix composites into a desired shape with accuracy has been a challenge for many years. Grinding is a process aimed at achieving better-quality surface finish along with reasonable rate of material removal. The present article describes the influence of operating parameters on the tangential grinding force, size effect, and surface integrity in the grinding of in situ aluminum matrix composites using various grinding wheels. The material removal mechanism of the in situ composite under different grinding conditions is established. Experimental results show that the grinding operating parameters have significant influence on the tangential grinding force, size effect, surface integrity, and material removal. Scanning electron and atomic force microscopy findings indicate presence of numerous surface defects on the grounded surface under all grinding conditions. Diamond grinding wheel outperformed the CBN and Al2 O3 wheels by requiring lower grinding force and specific grinding energy and generating lower surface defects. Surface defects, including grinding striation, delamination, and ridge formation are unavoidable under all machining conditions. However, the aforementioned surface defects indicate the ductile mode of material removal at all experimental conditions. Undeformed chip thickness under various grinding conditions plays a significant role in material removal and surface generation. These findings help to understand the mechanism of material removal in machining of in situ composites under various grinding conditions, which helps in attaining the economic production rate without compromising the surface integrity.